THE EFFECT OF SERVICE QUALITY AND PROMOTION ON THE DECISION TO BECOME A CUSTOMER WITH SATISFACTION AS AN INTERVENING VARIABLE AT BSI KCP MADIUN - Maulina, Latiffa Norria; Fitriani, Ajeng Pipit (Ar-Rihlah : Jurnal Keuangan dan Perbankan Syariah, 2026)
This study aims to analyze the effect of service quality and promotion on the decision to become a customer at Bank Syariah Indonesia KCP Madiun, with satisfaction as an intervening variable. This research uses a quantitative approach, which emphasizes numerical data measurement and statistical analysis to test hypotheses or answer research questions using a survey method, where data were collected through the distribution of questionnaires to 100 respondents who are customers of BSI KCP Madiun. Data analysis was conducted using multiple linear regression with the help of SPSS software. The analysis procedures include validity testing, reliability testing, classical assumption testing, t-test, F-test, and coefficient of determination (R²). The results show that service quality has a significant effect on the decision to become a customer as well as on satisfaction. On the other hand, promotion has a significant effect on the decision to become a customer but does not affect satisfaction. Furthermore, satisfaction has a significant effect on the decision to become a customer. However, satisfaction is able to mediate the relationship between service quality and the decision to become a customer, but it does not mediate the relationship between promotion and the decision to become a customer.